Communicating With Parents and Preschool Children: A Qualitative Exploration of Dental Professional-Parent-Child Interactions During Paediatric Dental Consultations to Prevent Early Childhood Caries - Yuan, Siyang; Humphris, Gerry; MacPherson, Lorna M. D.; Ross, Alistair L.; Freeman, Ruth (Frontiers in Public Health, 2021)
The aim of this study was to explore the communication interactions and styles adopted by dental professionals with parents and young children during dental consultations to prevent early childhood caries, by examining the transcriptions of video recordings in primary dental care. A secondary analysis of the transcribed data from video recordings of dental professionals, parents and preschool children when attending for preventive dental care were scrutinised. A conversation analytical approach was used to analyse the data. The transcriptions were read, examined and analysed independently to ensure the trustworthiness of the analysis. The transcriptions were explored for interactive patterns and sequences of interaction. Forty-four individual consultations between dental professionals, parents, and preschool children were recorded. The number of communication behaviours was 7,299, with appointment length ranging from 130 to 1,756 seconds. Two patterns of communication were identified as dyadic and triadic interactions within a continuous shifting cycle. The three styles of communication were social talking, containing worries and task-focusing. Social talking was characterised by shifts between dyadic and triadic communication interactions and symmetry of communication utterances and containing worries typified by the cyclical nature of the triadic and dyadic communication interactions, the adoption of talk-turn pairs, and treatment alliance formation. Task-focusing pattern and structure were different for dentists and extended-duty dental nurses. For dentists, task-focusing was characterised by a dyadic interaction and a symmetrical communication pattern whereas for extended-duty dental nurses, task-focusing was typified by symmetrical and asymmetrical communication patterns within dyadic and triadic interactions. Empathy and understanding of the young child’s emotional needs during containing worries allowed the formation of the treatment alliance and with the treatment alliance, the acceptance of interventions to prevent early childhood caries during ‘task-focusing’. This qualitative exploration suggests that dyadic and triadic, communication interactions of a dynamic and cyclical quality were exhibited during paedodontic consultations. The communication styles of social talking, containing worries and task-focusing were evident. Successful social talking signalled the entry to containing worries and triadic treatment alliance formation which permits the preventive goals of the consultation to be achieved (task-focusing). Future work should generate additional data to support the hypotheses created here.